1980
DOI: 10.1111/j.1525-1594.1980.tb03911.x
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of Hemofiltration to Hernodialysis for Treatment of Chronic Renal Failure: Comparative Studies Between Hernofiltration and Hernodialysis on Dialysis Disequilibrium Syndrome

Abstract: A significantly lower incidence of DDS, hypotension, and impending shock was found during and after hemofiltration as compared with conventional hemodialysis. Hemofiltration, in contrast to hemodialysis, showed less decrease of circulating plasma volume, mild change in plasma osmolality without red cell swelling, better compensation of acidosis despite less uptake of acetate, more stable PCO2 during the procedure, less paradoxical acidosis in cerebrospinal fluid, and a lower urea concentration gradient between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…Others reported that haemofiltration treatments were associated with a smaller decrease in circulating plasma volume, with less change in plasma osmolality without red cell swelling, and invasive sampling of cerebrospinal fluid was reported to show less paradoxical acidosis in cerebrospinal fluid, with a lower urea concentration gradient between cerebrospinal fluid and plasma [8]. It was therefore suggested that these changes resulted from improved mass transfer between compartments within the body during treatment with haemofiltration compared to HD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others reported that haemofiltration treatments were associated with a smaller decrease in circulating plasma volume, with less change in plasma osmolality without red cell swelling, and invasive sampling of cerebrospinal fluid was reported to show less paradoxical acidosis in cerebrospinal fluid, with a lower urea concentration gradient between cerebrospinal fluid and plasma [8]. It was therefore suggested that these changes resulted from improved mass transfer between compartments within the body during treatment with haemofiltration compared to HD.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in intra-session hypotension with convective techniques has at times been variously attributed to improved sympathetic nervous system activity [5], greater thermal losses [6], and relatively greater sodium retention [7]. As such haemofiltration has been reported to achieve faster mass transfer between compartments within the body with more rapid mass transfer both from the intracellular as well as from the extracellular space into the plasma [8]. Bioimpedance has been used to assess changes in extracellular water (ECW) and intracellular water (ICW) during dialysis sessions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since blood was purified at first in both methods, the circulating blood com partment was affected most. It is well known that the circulating blood volume decreases during both methods [3,5]. The change in serum protein concentration was measured in a separate experiment to estimate the change in circulating blood volume [5], A solid decrease in circulating blood volume was found in both methods, but the change was greater in HD.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that the circulating blood volume decreases during both methods [3,5]. The change in serum protein concentration was measured in a separate experiment to estimate the change in circulating blood volume [5], A solid decrease in circulating blood volume was found in both methods, but the change was greater in HD. It is assumed that a larger decrease in blood volume with a higher clear ance rate may give considerable influence on the disappearance rate in HD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation